Design and construction of sun tracking systems for solar parabolic concentrator displacement - Skouri, Safa; Ben Haj Ali, Abdessalem; Bouadila, Salwa; Ben Salah, Mohieddine; Ben Nasrallah, Sassi (Renewable & sustainable energy reviews, 2016)
Solar concentrator technology is becoming more prevalent today and studies performed on this subject have gained a great deal of interest in the world. In order to design a new solar parabolic concentrator that will be installed to operate in more efficient and more feasible way, it is necessary in the first step to analyze such parameters like solar irradiations values, and solar angles. Therefore, in this work, theoretical studies have been performed for solar angles using time and geographic parameters in Tunisia. An experimental measurement of solar irradiations has been done using a high precision metrological station to determine the diffuse, the direct and the global irradiations on the horizontal plane. In the second step each solar concentrator technology has its specifications in terms of mobility, orientation and the accuracy of the tracking system. In this work three pilot sun tracking systems for a solar parabolic concentrator were designed and constructed in the Research and Technology Center of Energy in Tunisia. Those trackers are able to follow the sun position on both axes (azimuth and elevation angles). We have described and determined the sun tracking errors of each one. A comparative study of the three sun tracking systems with a commercial tracker has been conducted. Basing on efficiency and economical criteria one of the sun tracking systems was selected. The total price of the chosen tracker is estimated to be around 1300 Euros and its tracking error is inferior to 0.2°. The advanced accuracy of the new tracker was achieved with the use of reduction gear unit.